Development of Creative Handicrafts Industrial Zones in Rajapolah District, Tasikmalaya Regency: Spatial Recommendation for Village Areas - Ari Djatmiko; Deden Syarifudin; Zulphiniar Priyandoko; Meyliana Lisanti; Tyara Kusuma Diena (Geosfera Indonesia, 2021)
The creative craft industry in Rajapolah District as the main driver of the regional economy in supporting facilities that still concentrated in one particular area. There have been limited studies concerned on spatial functions in creative spaces. This article addresses the criteria for functions and facilities for the development of creative industrial areas and their application in spatial recommendation for village areas. This research used a quantitative method using instruments on statistical data. Data analysis was divided into three stages namely identification, determining the criteria, and determining spatial functions. The study used the form of production data includes raw materials, labor, product size, product diversity, as well as the distribution of production houses, marketing facilities and education and training. The results showed that the development of creative industrial zones can be identified on criteria functions in the provision of raw materials, production, research and development, and marketing. Some villages have fulfilled the criteria for the function of creative spaces, which are relatively scattered in craft production houses close to the center of village activities. Besides that, it is also relatively far away, however supported by adequate road access. Creative promotion centers in the form of markets, outlets and shops are mostly concentrated on the main road network. Meanwhile, creative education centers in the form of multi-purpose building are relatively concentrated in some villages. Articles contribute to the field of creative industry science which is practically used as a consideration for the government in preparing detailed urban masterplans. Keywords: Creative industry; Handicrafts; Spatial; Development zone Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License